Influence of Management Structure on Performance of Kwara United Football Club in Nigeria Premier League - Ajadi Memunat Tunrayo (Indonesian Journal of Sport Management, 2022)
The study investigated influence of management structure on performance of Kwara United football club in Nigeria premier league. Descriptive research design of survey type was used. The population comprised of all coaches, management staff and players of kwara united. Purposive sampling technique was used to select 115 respondents. Researcher structure questionnaire was adopted for the study. The instrument was validated by experts and tested for reliability using Pearson Product Moment Correlation (PPMC). Correlation coefficient of 0.68 was obtained. The administrator of instrument was done by the researcher and three (3) trained research assistants. The data collected were analysis using inferential statistics of chi-square (x2) to test the formulated hypotheses set for the study at 0.05 alpha level. The result revealed that internal crisis, leadership style and appointments of people into the board have significant influence on performance of kwara united in Nigeria premier league. The study therefore recommends that management should not give room for conflict of interest to generate into internal crisis that would affect club performances. Moreso appointment into the board should be based on merit so as to enhance effective performance of football clubs in the league.